The increasing incidence and prevalence of hypereosinophilic syndrome in the United Kingdom - Gema Requena; John Logie; Daniel C. Gibbons; Jonathan Steinfeld; Melissa K. Van Dyke (Immunity, Inflammation and Disease, 2021)
Abstract Introduction Data on the burden of hypereosinophilic syndrome (HES) are limited. This study investigated the incidence and prevalence of HES using real‐world data from patients in the United Kingdom. Methods Primary care data from the Clinical Practice Research Datalink were analyzed. The patients of interest were identified using medical codes specific for HES. Annual incidence rates and prevalence were estimated for the years 2010–2018 (inclusive) using patients observed for a minimum period of one year. Results Between 2010 and 2018, 93 patients were identified with HES. During the study period the incidence of HES ranged from less than 0.04, 95% confidence interval (CI) (0.01–0.07) to 0.17, 95% CI (0.10–0.26) per 100,000 person‐years and the prevalence ranged from 0.15, 95% CI (0.10–0.25) to 0.89, 95% CI (0.74–1.09) cases per 100,000 persons. Sensitivity analyses varying the minimum observation period required to identify HES patients gave similar results. Conclusion These results provide estimates of the burden of HES in the United Kingdom and indicate that whilst HES is a very rare disease, there is evidence that is increasingly being recorded in UK primary care.